Enhancing Recount Text Writing Skills of EFL Students through Project-Based Learning - Putri, Pande Ketut Raina Murdia (English Education Department STKIP Agama Hindu Singaraja, 2025)
This study investigates the impact of Project-Based Learning (PBL) on enhancing students’ writing skills, focusing particularly on the revision process. Conducted over two cycles, the research employed pre-test and post-test assessments, classroom observations, and self-evaluation checklists to gather data. The findings reveal a significant improvement in students’ writing abilities, with the average writing score increasing from 25.43 in the first cycle to 31.89 in the second cycle, reaching the